Silicon nitride substrate
Patent Information
- Application Number
- JP2024144121
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-30
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-14
AI Technical Summary
【0008】 本発明の窒化ケイ素基板により、熱伝導性や誘電損失の温度依存性を低減することが可能となり、信頼性に優れた窒化ケイ素基板を提供することが可能となる。
Smart Images

Figure 2025036246000002 
Figure 2025036246000003 
Figure 2025036246000004
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon nitride substrates. [Background technology]
[0002] Silicon nitride has excellent mechanical strength, thermal conductivity, and electrical insulation properties, and is therefore used in substrates for semiconductor modules, etc. For a substrate to have high reliability, it is important that it has high uniformity.
[0003] Regarding the uniformity of silicon nitride substrates, for example, Patent Document 1 proposes a silicon nitride substrate with small compositional differences between the center and edges of the substrate surface. Specifically, the amounts of magnesium, yttrium, and oxygen are measured at the center and edges of the substrate surface, and the silicon nitride substrate has small differences between the center and edges, and it describes how the distribution of auxiliary agents is made extremely uniform from a macroscopic perspective, thereby making it possible to stably suppress warping of the silicon nitride substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2020 / 203787 issue Summary of the Invention [Problem to be solved by the invention]
[0005] As in Patent Document 1, it is possible to control warpage by controlling uniformity from a macroscopic point of view and reducing the difference in the amount of auxiliary agent and oxygen between the center and the edge of the silicon nitride substrate. On the other hand, since thermal conductivity, electrical properties, and the like are dependent on silicon nitride particles and auxiliary phases, in order to achieve high reliability in these properties, it is necessary to consider uniformity from a microscopic point of view at the microstructure level of silicon nitride particles, auxiliary phases, and the like. Therefore, an object of the present invention is to provide a silicon nitride substrate having high uniformity at the microstructure level. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors have conducted extensive research. As a result, they have found that a silicon nitride substrate having high uniformity at the microstructural level can be obtained by controlling the raw material silicon nitride powder and the sintering conditions. They have also confirmed that the uniformity at the microstructural level can be evaluated by a nanoindentation test, and have completed the present invention.
[0007] That is, the present invention provides a silicon nitride substrate in which, in a hardness distribution obtained by a nanoindentation test under a load of 0.5 mN, the ratio R1 (HA10 / HA90) of the cumulative 10% hardness HA10 in the hardness region of less than 15.00 GPa to the cumulative 90% hardness HA90 in the hardness region of less than 15.00 GPa is 0.25 or more, and the ratio R2 (HS10 / HS90) of the cumulative 10% hardness HS10 in the hardness region of 15.00 GPa or more to the cumulative 90% hardness HS90 in the hardness region of 15.00 GPa or more is 0.52 or more. Effect of the Invention
[0008] The silicon nitride substrate of the present invention makes it possible to reduce the temperature dependence of thermal conductivity and dielectric loss, and thus makes it possible to provide a silicon nitride substrate with excellent reliability. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a cross-sectional view of a firing container used in Example 1 of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view of a firing container used in Example 2 of the present invention. [Diagram 3] FIG. 1 is a cross-sectional view of a firing container (a firing container that has been widely used in the past) used in Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the silicon nitride substrate of the present invention, in a hardness distribution obtained by a nanoindentation test under a load of 0.5 mN, the ratio R1 (HA10 / HA90) of the cumulative 10% hardness HA10 in the hardness range of less than 15.00 GPa to the cumulative 90% hardness HA90 in the hardness range of less than 15.00 GPa is 0.25 or more, and the ratio R2 (HS10 / HS90) of the cumulative 10% hardness HS10 in the hardness range of 15.00 GPa or more to the cumulative 90% hardness HS90 in the hardness range of 15.00 GPa or more is 0.52 or more.
[0011] Nanoindentation testing uses a tiny indenter to measure indentation hardness, making it possible to evaluate microscopic regions. Normally, silicon nitride substrates contain silicon nitride particles and an auxiliary phase derived from a sintering aid. If the silicon nitride particles and the auxiliary phase are homogeneous, it can be said that the substrate has high uniformity at the microstructure level. In addition, in order to prevent the influence of surface unevenness, nanoindentation testing must be performed with the surface roughness of the test specimen being 0.2 μm or less. If the surface roughness is 0.2 μm or less, evaluation can be performed with almost no influence from surface unevenness. The surface roughness of the test specimen can be reduced to 0.2 μm or less by mirror finishing.
[0012] Through the study of the present inventors, it was found that the uniformity of each of the silicon nitride particles and the auxiliary phase can be evaluated by a nanoindentation test. That is, by performing a nanoindentation test under the condition of a load of 0.5 mN, a hardness distribution of a micro-area can be obtained. The hardness reflects the properties of the silicon nitride particles or the auxiliary phase at each measurement point, and if the hardness distribution is sharp, it can be said that the uniformity is high. In general, the silicon nitride particles and the auxiliary phase have different hardnesses, and the silicon nitride particles have a higher hardness. In the nanoindentation test under the above conditions, it was considered that the properties of the silicon nitride particles can be evaluated by the hardness region of 15.00 GPa or more, and the properties of the auxiliary phase can be evaluated by the hardness region of less than 15.00 GPa. And, if the hardness distribution is sharp, that is, if the ratio of the cumulative 10% hardness to the cumulative 90% hardness (the value obtained by dividing the cumulative 10% hardness by the cumulative 90% hardness) is large, it can be said that the uniformity is high.
[0013] In the present invention, the term "cumulative 10% hardness" refers to the hardness that is 10% cumulative from the smallest when the measurement data of hardness obtained in the hardness range, i.e., hardness of 15.00 GPa or more and hardness of less than 15.00 GPa, are rearranged in ascending order of hardness. Similarly, the term "cumulative 90% hardness" refers to the hardness that is 90% cumulative from the smallest when the measurement data obtained are rearranged in ascending order of hardness. Specifically, when n measurement data are obtained, the 0.1nth hardness value is the cumulative 10% hardness when the data are arranged in ascending order of hardness, and the 0.9nth hardness value is the cumulative 90% hardness. In addition, when 0.1n and 0.9n are not integers, the cumulative 10% hardness and the cumulative 90% hardness may be obtained by rounding them to integers.
[0014] As described above, the properties of the auxiliary phase can be evaluated by the region of hardness less than 15.00 GPa, so that the hardness distribution obtained by the nanoindentation test is evaluated by calculating the ratio R1 (HA10 / HA90) of the cumulative 10% hardness (HA10) in the region of hardness less than 15.00 GPa to the cumulative 90% hardness (HA90) in the region of hardness less than 15.00 GPa. The silicon nitride substrate of the present invention has R1 of 0.25 or more, preferably 0.26 or more, and more preferably 0.27 or more. The upper limit of R1 is not particularly limited and may be any value less than 1.00, which is the theoretical maximum value, but is usually 0.90 or less, particularly 0.75 or less, and even 0.50 or less.
[0015] In addition, since the properties of silicon nitride particles can be evaluated by the hardness range of 15.00 GPa or more, the hardness distribution obtained by the nanoindentation test is evaluated by calculating the ratio R2 (HS10 / HS90) of the cumulative 10% hardness (HS10) in the hardness range of 15.00 GPa or more to the cumulative 90% hardness (HS90) in the hardness range of 15.00 GPa or more. The silicon nitride substrate of the present invention has R2 of 0.52 or more. The upper limit of R2 is not particularly limited and may be any value less than 1.00, which is the theoretical maximum value, but is usually 0.90 or less, particularly 0.75 or less.
[0016] If R1 and R2 are within the above ranges, it can be said that the silicon nitride substrate has high uniformity at the microstructure level of the silicon nitride particles and the auxiliary phase.The silicon nitride substrate has small temperature dependence of thermal conductivity and dielectric loss.The reason for this is not clear, but the inventors believe it to be as follows.
[0017] The thermal conductivity is strongly influenced by the internal structure of the silicon nitride substrate, specifically, the organizational structure of the silicon nitride particles and auxiliary phase that constitute the silicon nitride substrate, and it is important that the path for heat transmission is sufficiently secured. Therefore, if the internal structure of the silicon nitride substrate changes significantly, the path for heat transmission may change and the thermal conductivity may decrease significantly. If the temperature changes, the internal structure of the silicon nitride substrate also changes due to expansion and contraction. In this case, if the internal structure of the silicon nitride substrate is uniform at a microscopic level, the change is likely to occur uniformly and the path for heat transmission is unlikely to be significantly destroyed, but if the internal structure of the silicon nitride substrate is not uniform at a microscopic level, a large change in the internal structure occurs locally, and the path for heat transmission is likely to be significantly destroyed. As a result, it is presumed that the temperature dependence of the thermal conductivity becomes larger when the internal structure of the silicon nitride substrate is not uniform at a microscopic level compared to when the internal structure of the silicon nitride substrate is uniform at a microscopic level. Dielectric loss is also strongly affected by the internal structure of the silicon nitride substrate, and it is presumed that when changes in the internal structure due to temperature are small, that is, when the internal structure of the silicon nitride substrate is uniform at a microscopic level, the temperature dependence of dielectric loss will be small.
[0018] The silicon nitride substrate of the present invention has silicon nitride particles and an auxiliary phase as described above. The auxiliary phase is composed of components derived from a sintering auxiliary. The blending ratio of the silicon nitride particles and the auxiliary phase is not particularly limited, but if the auxiliary phase is too little, sintering may be insufficient and mechanical properties such as strength may be insufficient, and if the auxiliary phase is too much, the advantages of the silicon nitride substrate may not be fully exhibited. Therefore, in the hardness distribution obtained by the nanoindentation test, the number of points having a hardness of 15.00 GPa or more is preferably 60% or more, more preferably 70% or more, and preferably 95% or less, more preferably 90% or less.
[0019] The silicon nitride substrate of the present invention has a thermal conductivity (λ 25℃) is preferably 50 W / m·K or more, more preferably 70 W / m·K or more, and even more preferably 90 W / m·K or more. The silicon nitride substrate of the present invention has a thermal conductivity (λ 250℃ ) and the λ 25℃ Ratio to (λ 250℃ / λ 25℃ ) is preferably 0.60 or more, and more preferably 0.70 or more. 250℃ / λ 25℃ The closer to 1.00 the thermal conductivity is, the smaller the temperature dependence of the thermal conductivity is. In general, the thermal conductivity of silicon nitride decreases as the temperature increases, so λ 250℃ / λ 25℃ is less than or equal to 1.00. The thermal conductivity can be measured by the laser flash method.
[0020] The silicon nitride substrate of the present invention has a dielectric loss (ε 25℃ ) and dielectric loss λ at 250℃ 250℃ Ratio to (ε 250℃ / ε 25℃ ) is preferably 0.60 or more and 1.40 or less, and more preferably 0.70 or more and 1.30 or less. 250℃ / ε 25℃ It can be said that the closer to 1.00, the smaller the temperature dependence of dielectric loss.
[0021] The silicon nitride substrate of the present invention preferably has a three-point bending strength of 600 MPa or more. Also, the fracture toughness value is 6.0 MPa m 1 / 2 More preferably, it is equal to or greater than this.
[0022] The silicon nitride substrate of the present invention is preferably plate-shaped. The size of the main surface is not particularly limited, but if the size is too large, it becomes difficult to improve uniformity, so the main surface is preferably rectangular and is 200 mm x 200 mm or less, more preferably 100 mm x 100 mm or less. The lower limit of the size of the main surface is preferably 10 mm x 10 mm or more, which is easy to process for nanoindentation measurement. In addition, the ratio of the length of the long side to the short side of the main surface is not particularly limited. The thickness of the silicon nitride substrate of the present invention is not particularly limited, but is generally 0.1 mm to 2.0 mm.
[0023] The silicon nitride substrate of the present invention can be easily obtained by a method for producing a silicon nitride substrate including at least the steps of: a water vapor heat treatment step of exposing silicon nitride powder to water vapor under heating and an oxygen-containing atmosphere; a mixing step of mixing the silicon nitride powder obtained in the water vapor heat treatment step with a sintering aid powder to obtain a raw material mixture; a molding step of obtaining a molded body of a desired shape from the raw material mixture; and a firing step of firing the molded body at 1700°C to 1900°C in the presence of 5.0 g or more of an atmospheric adjuster per 100 g of molded body.
[0024] The steam heating process is a process in which silicon nitride powder is exposed to steam under heating and oxygen-containing atmosphere. It is believed that this process adjusts the surface of the silicon nitride powder to a stable and uniform state, thereby obtaining a silicon nitride substrate with high uniformity at the microstructure level. The reason is unclear, but the inventors speculate as follows. That is, oxygen is required for sintering silicon nitride, and the auxiliary component reacts with oxygen to generate a liquid phase, which is then densified by liquid phase sintering. Therefore, it is believed that if there is variation in the surface oxidation state of the silicon nitride powder, there will be variation in the sintering reaction, and the uniformity at the microstructure level will decrease. The oxidation of silicon nitride powder also progresses due to thermal and mechanical loads during the manufacturing process of the silicon nitride substrate, such as mixing with sintering auxiliary agents, molding, and firing. Oxidation due to loads in such manufacturing processes is difficult to control, and surface oxidation state is likely to vary. Here, by performing a steam heating process in advance before firing, the oxidation of the surface of the silicon nitride powder will progress sufficiently. This makes it difficult for oxygen to reach the silicon nitride portion, making it less likely for oxidation to occur due to the stress during the manufacturing process, and therefore less likely for variation in the progress of oxidation to occur due to the stress during the manufacturing process. As a result, it is believed that variation in the sintering reaction is suppressed, making it possible to obtain a silicon nitride substrate with high uniformity at the microstructural level.
[0025] The steam heating treatment may be performed by exposing the silicon nitride powder to steam under heating. Specifically, the silicon nitride powder and water may be placed in a covered container and heated to a temperature at which steam is generated in an oxygen-containing atmosphere or higher. The amount of water placed in the sealed container may be equal to or higher than the amount of the silicon nitride powder. The heating temperature may be 100°C or higher at which steam is generated, but from the viewpoint of performing the treatment reliably and efficiently, it is preferably 250°C to 700°C, more preferably 400°C to 600°C. From the viewpoint of performing the treatment reliably and efficiently, the time of the steam heating treatment is preferably 10 minutes to 200 minutes, more preferably 30 minutes to 100 minutes. The atmosphere during the steam heating treatment may be an oxygen-containing atmosphere, and may be air. The covered container may be filled with steam, and may not be completely sealed. The silicon nitride powder and water may be placed in a container with an open top, such as a tray, and placed in the covered container.
[0026] The silicon nitride powder may be made of α-type silicon nitride, β-type silicon nitride, or a mixture of these, but it is preferable to include β-type silicon nitride because β-powder is less likely to undergo grain growth during sintering than α-powder and is easier to control uniformity. The β-type rate of the silicon nitride powder is preferably 80% or more, more preferably 90% or more, and more preferably 99% or more. The β-type rate of the silicon nitride powder means the peak intensity ratio of the β-phase to the total of the α-phase and β-phase in the silicon nitride powder [100 x (peak intensity of β-phase) / (peak intensity of α-phase + peak intensity of β-phase)], and is determined by powder X-ray diffraction (XRD) measurement using CuKα rays. More specifically, it is determined by calculating the weight ratio of the α-phase and β-phase in the silicon nitride powder according to the method described in C.P. Gazzara and D.R. Messier: Ceram. Bull., 56 (1977), 777-780.
[0027] The particle size of the silicon nitride powder is not particularly limited, but the average particle size D50 is preferably 0.5 to 3.0 μm, more preferably 1.0 to 2.0 μm. The specific surface area of the silicon nitride powder is preferably 7 to 20 m.2 / g, and 12 to 15m 2 In the present invention, the specific surface area refers to a BET specific surface area measured by a BET single point method using nitrogen gas adsorption.
[0028] The sintering aid powder may be any known powder without any particular limitation, and examples thereof include oxides such as yttria, magnesia, ceria, and calcia, as well as compounds not containing oxygen, such as carbonitride compounds and nitride compounds. Examples of carbonitride compounds include Y2Si4N6C, Yb2Si4N6C, Ce2Si4N6C, and MgSi4N6C. Examples of nitride compounds include MgSiN2.
[0029] The silicon nitride powder and the sintering aid powder are mixed to obtain a raw material mixture. The mixing method is not particularly limited, and for example, each component may be weighed out in a predetermined blending amount and mixed in a dry state, or mixed in a wet state using a dispersion medium. Examples of mixing devices for dry mixing include a dry bead mill and an attritor. Examples of mixing devices for wet mixing include an ultrasonic dispersion device, a bead mill, a ball mill, a roll mill, a homomixer, an ultramixer, a dispersing mixer, a penetrating type high-pressure dispersion device, a collision type high-pressure dispersion device, a multi-hole type high-pressure dispersion device, a trapping type high-pressure dispersion device, a (collision + penetrating) type high-pressure dispersion device, and an ultra-high-pressure homogenizer. Examples of dispersion media for wet mixing include water, alcohol, toluene, and the like.
[0030] The raw material mixture may contain other components in addition to the silicon nitride powder and the sintering aid powder, such as the dispersion medium, a binder, a dispersant, a plasticizer, and a defoamer.
[0031] Examples of the binder include polyvinyl alcohol, polyvinyl acetal, polyvinylpyrrolidone, acrylic resin, polyacrylamide, urethane resin, polyester, polyether, melamine, epoxy resin, cellulose resin, and starch. These binders can be used alone or in combination of two or more. The amount of the binder can be appropriately selected, and can be selected from the range of, for example, usually 1 to 30 parts by mass, particularly 10 to 25 parts by mass, relative to 100 parts by mass of the total amount of the silicon nitride powder and the sintering aid powder.
[0032] The dispersant is used to enhance the dispersibility of the total amount of silicon nitride powder and sintering aid powder in the molding composition, and generally, a surfactant can be suitably used. As the surfactant, any known surfactant can be used without any restrictions. Specific examples of surfactants that can be suitably used in the present invention include carboxylated trioxyethylene tridecyl ether, diglycerol monooleate, diglycerol monostearate, carboxylated heptaoxyethylene tridecyl ether, tetraglycerol monooleate, hexaglycerol monooleate, sorbitan laurate, sorbitan oleate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and the like. These surfactants may be used alone or in combination of two or more. The amount of the dispersant can be appropriately selected, and can be selected, for example, from the range of 0.1 to 5 parts by mass per 100 parts by mass of the total amount of the silicon nitride powder and the sintering aid powder. Within this range, the upper limit of the amount of dispersant is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less.
[0033] In the molding step, a molded body having a desired shape is obtained from the raw material mixture obtained in the mixing step. The molding method for obtaining the molded body is not particularly limited, and for example, the raw material mixture is molded by press molding, a slurry of the raw material mixture containing a dispersion medium is dried with a spray dryer or the like to obtain granules, or a slurry of the raw material mixture containing a dispersion medium is molded into a sheet by a doctor blade method or the like. Among these, the sheet molding by the doctor blade method is preferred because it can be easily produced.
[0034] When the molded body obtained in the molding process contains organic components such as a dispersion medium, a binder, a dispersant, a plasticizer, and an antifoaming agent, drying to remove the dispersion medium and degreasing to remove the binder, etc., may be performed before the firing process in order to facilitate firing. The drying conditions are not particularly limited, but for example, when the dispersion medium is water, the molded body may be heated to about 30°C to 150°C. The degreasing conditions are not particularly limited, but for example, the molded body may be heated to 450°C to 650°C in air or in an inert atmosphere such as nitrogen or argon.
[0035] In the firing step of the present invention, the molded body is fired at 1700°C to 1900°C in the presence of 5.0 g or more of an atmosphere adjuster per 100 g of the molded body. The atmosphere adjuster is used to prevent the volatilization of the auxiliary components, and specifically, an atmosphere adjuster having the same chemical composition as the sintering aid powder or an oxide of a metal element contained in the sintering aid is used. For example, when yttria is used as the sintering aid, yttria is used as the atmosphere adjuster, and when Y2Si4N6C is used as the sintering aid, Y2Si4N6C or yttria is used as the atmosphere adjuster.
[0036] When multiple compounds are used as the sintering aid powder, the difference between the abundance ratio of the metal elements contained in the atmosphere adjuster and that of the sintering aid powder may be adjusted to within 20%. In this case, a compound having the same chemical composition as the sintering aid powder or an oxide of the metal elements contained in the sintering aid may be mixed in a desired abundance ratio and used, or each may be placed in the firing vessel to achieve the desired abundance ratio.
[0037] In general, volatilization of sintering aids occurs randomly during the firing process. In order to improve the uniformity of silicon nitride substrates, it is necessary to control the volatilization of sintering aids. It is presumed that by using an atmosphere adjuster, the atmosphere adjuster volatilizes during firing and fills the firing vessel, suppressing the volatilization of sintering aids and improving the uniformity of silicon nitride substrates.
[0038] It is important that the firing step is carried out in the presence of 5.0 g or more of an atmosphere adjusting agent per 100 g of the molded body. If the amount of the atmosphere adjusting agent is small, the volatilization of the sintering aid cannot be sufficiently controlled, and uniformity at the microstructure level cannot be obtained. The amount of the atmosphere adjusting agent is preferably 5.0 g or more per 100 g of the molded body, and more preferably 7.0 g or more. There is no particular upper limit to the amount of the atmosphere adjusting agent, but if it is too much, the manufacturing efficiency is poor, so it is preferably 15.0 g or less, more preferably 10.0 g or less per 100 g of the molded body.
[0039] The atmosphere control agent may be in the form of a powder or a bulk material, but is preferably in the form of a powder, since it volatilizes efficiently and fills the firing vessel easily. When the atmosphere control agent is in the form of a powder, the particle size is preferably 1.0 μm to 2.0 μm, from the viewpoint of efficiently filling the firing vessel.
[0040] In the firing process of the present invention, it is also important to increase the airtightness of the firing vessel. If the firing vessel is not airtight, the volatilized atmosphere control agent will not sufficiently fill the firing vessel, resulting in a decrease in the uniformity of the silicon nitride substrate.
[0041] As the firing container, for example, a firing container having a cross-sectional view as shown in FIG. 1 or FIG. 2 can be used. The firing container shown in FIG. 1 has a container part 1 and a lid part 2, and has two corners at a connection part 3 between the container part 1 and the lid part 2. The firing container shown in FIG. 2 has a different structure of the connection part 3 from that shown in FIG. 1, but also has two corners. A firing container that has been widely used in the past (FIG. 3) has only one corner at the connection part between the container part and the lid part. By increasing the number of corners at the connection part, it becomes difficult for gas inside the firing container to be released to the outside of the firing container through the connection part, improving airtightness.
[0042] The firing container may have three or more corners, but since the manufacturing and maintenance of the firing container becomes time-consuming when the number of corners is large, the number of corners is preferably 5 or less, and more preferably 3 or less. The angle of the corner may be more acute or obtuse than 90°, but from the viewpoint of ensuring airtightness and ease of manufacturing and maintenance of the firing container, it is preferably 45° to 135°, and more preferably 80° to 100°. In addition, since the shape of the container side and the shape of the lid side at the connection part are the same due to the need for sealing, the angle of the container side and the angle of the lid side are summed to 360°, but the angle of the corner is the smaller value of the angle of the container body side and the angle of the lid side.
[0043] In the firing container, the length of the connection part 3 is preferably 2.0 mm or more, more preferably 4.0 mm or more. By lengthening the connection part, it becomes difficult for the gas inside the firing container to be released to the outside of the firing container through the connection part, and it becomes easy to improve the airtightness. There is no particular limit to the upper limit of the length of the connection part 3, but if it is made longer, the firing container becomes large and manufacturing and handling become difficult, so it is usually 5.0 mm or less, particularly 4.5 mm or less. The length of the connection part is the shortest length from the inside to the outside of the container at the part where the container part 1 and the lid part 2 of the firing container are in contact. As described above, the shape of the container part side and the shape of the lid part side of the connection part are the same, so the length of the connection part may be measured on the container part side.
[0044] The volume of the firing vessel is not particularly limited, but in order to make it easier to fill the firing vessel with the volatilized atmosphere control agent, the volume of the firing vessel is set to 5250 m per 100 g of atmosphere control agent. 3 Below, especially 5000m 3 The lower limit of the volume of the firing vessel is not particularly limited, but if it is too small, the internal pressure increases due to the volatilized atmospheric control agent, making it difficult to handle. Therefore, the volume of the firing vessel per 100 g of atmospheric control agent is preferably 2500 m 3 Above, especially 2600m 3 It is preferable that the amount is equal to or more than that.
[0045] The firing temperature is 1700°C to 1900°C, preferably 1820°C to 1880°C. The firing time is not particularly limited, but is preferably 1 to 30 hours, particularly 3 to 20 hours. The firing is preferably performed in an inert atmosphere. The firing pressure may be normal pressure or may be increased pressure. EXAMPLES
[0046] In the following, examples are described in order to specifically explain the present invention, but the present invention is not limited to these examples. The measurements of the various items in the examples and comparative examples were performed by the following methods.
[0047] (1) Measurement of hardness distribution by nanoindentation test A silicon nitride substrate was cut into 10 mm x 10 mm to obtain a test piece. Next, the main surface was mirror-finished, and the surface roughness of the main surface of the test piece was processed to 0.2 μm or less. The surface roughness of the test piece was measured at five points in an arbitrary 1000 μm x 1000 μm test area of the test piece using a non-contact three-dimensional measuring device (Keyence Corporation: VR-5000), and it was confirmed that Ra was 0.2 μm or less in all test areas. A nanoindentation test was performed on the mirror-finished surface of the test piece by pressing an indenter into 3600 points in a range of 30 μm x 30 μm at equal intervals under a load of 0.5 mN in air, to determine the microhardness. The nanoindentation test was performed at five points near the center and near the four corners of the main surface of the test piece, and the hardness distribution of the microregion was obtained from the results.
[0048] (2) Evaluation of temperature dependence of thermal conductivity After blasting the surface of the silicon nitride substrate, the surface was coated with Au and carbon. The thermal conductivity was then measured at 25°C, and then heated to 250°C to measure the thermal conductivity. From the results, the thermal conductivity λ at 25°C was calculated. 25℃ and thermal conductivity λ at 250℃ 250℃ Ratio to (λ 250℃ / λ 25℃ ) was obtained and the temperature dependence of thermal conductivity was evaluated. 250℃ / λ 25℃ The closer it is to 1.00, the smaller the temperature dependence. The thermal conductivity of the silicon nitride substrate was calculated by multiplying the thermal diffusivity, density, and specific heat, and was measured by the laser flash method using an Advance Riko Co., Ltd. TC-9000. The specific heat of the silicon nitride substrate was set to 0.68 (J / g K). The density of the silicon nitride substrate was measured using an automatic hydrometer (Shinko Denshi Co., Ltd.: DMA-220H type).
[0049] (3) Evaluation of temperature dependence of dielectric loss The silicon nitride substrate was cut into 42 mm x 42 mm test pieces, and the dielectric loss was measured. From the results, the temperature dependence of the dielectric loss was evaluated. The temperature dependence of dielectric loss was measured at 1MHz at 25℃, then heated to 250℃ and measured. From the results, the dielectric loss at 25℃, ε 25℃ and dielectric loss ε at 250℃ 250℃ Ratio to (ε 250℃ / ε 25℃ ) was calculated and evaluated. 250℃ / ε 25℃ The closer it is to 1.00, the smaller the temperature dependence. The dielectric loss was measured using an HP4192A LF impedance analyzer (Agilent), an HP-16047C test fixture (Agilent), electrode dimensions: φ24 mm, and guard electrode inner diameter: φ26 mm.
[0050] The silicon nitride substrate was manufactured using the following raw materials containing silicon nitride powder and a sintering aid.
[0051] <Silicon nitride powder> Silicon nitride powder X produced in a similar manner to silicon nitride powder A described in the examples of WO2021 / 107021. ·Betaization rate: 99% ·Average particle size D50: 1.8μm <Sintering aid> - Yttria (manufactured by Shin-Etsu Chemical Co., Ltd.) Magnesia (manufactured by Ube Material Industries, Ltd.) <Binders and dispersants> Binder: Acrylic resin (manufactured by Fujikura Kasei Co., Ltd.) Dispersant: Cerna D735 (manufactured by Chukyo Yushi Co., Ltd.)
[0052] <Example 1> A vat containing silicon nitride powder X and a vat containing water twice the amount of silicon nitride powder were placed in a thermostatic chamber, heated to 500°C, and left to stand for 1 hour, whereby a steam heating treatment was performed to obtain silicon nitride powder Y. Next, 100 parts by mass of silicon nitride powder Y, 5 parts by mass of yttria, 3 parts by mass of magnesia, and 0.5 parts by mass of dispersant were weighed, and mixed in a ball mill for 24 hours using water as a solvent and a resin pot and silicon nitride balls. The water was weighed in advance so that the concentration of the slurry was 60% by mass, and was poured into the resin pot. After the mixing, 22 parts by mass of binder was added, and mixing was performed for another 12 hours to obtain a slurry-like molding composition. Next, the molding composition was defoamed using a vacuum defoamer (manufactured by Sayama Riken Co., Ltd.), and the viscosity was adjusted to prepare a coating slurry. Thereafter, the viscosity-adjusted coating slurry was used to form a sheet by a doctor blade method, and the sheet was dried in air at 100° C. to evaporate the solvent, yielding a green sheet having a width of 750 mm and a thickness of 420 μm. The green sheet obtained as described above was subjected to a degreasing treatment at a temperature of 550° C. in dry air to obtain a degreased green sheet. The degreased green sheet was then cut into a 100 mm × 100 mm piece, placed in a sintering vessel, and sintered at 1,880°C for 9 hours in a nitrogen atmosphere under a pressure of 0.9 MPa·G to obtain a silicon nitride substrate. The firing vessel used was the one shown in FIG. 1, which had two corners at the connection portion and had a length of 4.0 mm. Furthermore, 5 g of yttria and 3 g of magnesia were present in the firing vessel as atmospheric adjusters per 100 g of green sheet (molded body). The evaluation results of the obtained silicon nitride substrate are shown in Table 1. In the nanoindentation test, 4915 locations had a hardness of less than 15.00 GPa, and 13085 locations had a hardness of 15.00 GPa or more.
[0053] <Example 2> A silicon nitride substrate was obtained in the same manner as in Example 1, except that a container having two corners at the connection portion, the length of which was 4.0 mm, as shown in Fig. 2 was used as the firing container. The evaluation results of the obtained silicon nitride substrate are shown in Table 1. In the nanoindentation test, 5730 locations had a hardness of less than 15.00 GPa, and 12270 locations had a hardness of 15.00 GPa or more.
[0054] <Comparative Example 1> A silicon nitride substrate was obtained in the same manner as in Example 1, except that a container having one corner at the connection portion and a length of 2.0 mm as shown in Fig. 3 was used as the firing container. The evaluation results of the obtained silicon nitride substrate are shown in Table 1. In the nanoindentation test, 6180 points had a hardness of less than 15.00 GPa, and 11820 points had a hardness of 15.00 GPa or more.
[0055] <Comparative Example 2> A silicon nitride substrate was obtained in the same manner as in Example 1, except that no water vapor heating treatment was performed and silicon nitride powder X was used. The evaluation results of the obtained silicon nitride substrate are shown in Table 1. In the nanoindentation test, 5030 locations had a hardness of less than 15.00 GPa, and 12970 locations had a hardness of 15.00 GPa or more.
[0056] [Table 1] [Explanation of symbols]
[0057] 1 Container part 2 Lid 3 Connection part
Claims
[Claim 1] A silicon nitride substrate, in which, in a hardness distribution obtained by a nanoindentation test under a load of 0.5 mN, a ratio R1 (HA10 / HA90) of a cumulative 10% hardness HA10 in a region where the hardness is less than 15.00 GPa to a cumulative 90% hardness HA90 in a region where the hardness is less than 15.00 GPa is 0.25 or more, and a ratio R2 (HS10 / HS90) of a cumulative 10% hardness HS10 in a region where the hardness is 15.00 GPa or more to a cumulative 90% hardness HS90 in a region where the hardness is 15.00 GPa or more is 0.52 or more.
Citation Information
Patent Citations
Silicon nitride substrate, silicon nitride-metal complex, silicon nitride circuit board, and semiconductor package
WO2020203787A1